Analyst of Digital Banking in Digital Transformation - Revy Amyneva Gulnoria; Khansa Shabihah; Rozihan (JAS (Jurnal Akuntansi Syariah), 2025)
The rapid growth of digital banking presents both opportunities and challenges for Islamic banking in Indonesia, particularly due to the relatively low levels of Islamic financial literacy and inclusion compared to conventional banking. This study aims to analyze the effect of digital transformation on Islamic financial inclusion, with adherence to sharia principles as a moderating variable that may strengthen or weaken this relationship. The study adopted a quantitative associative approach with an explanatory design, using secondary data obtained from the annual reports of Islamic Commercial Banks from 2020 to 2025. The data were analyzed using Moderated Regression Analysis (MRA). The results indicate that digital transformation has a significant positive influence on Islamic financial inclusion. In contrast, sharia compliance shows a significant negative effect. However, the interaction between the two variables is statistically significant, suggesting that sharia compliance strengthens the relationship between digital transformation and inclusion. These findings highlight the importance of integrating sharia values in digital strategies to ensure inclusive, trusted, and sustainable Islamic banking services in the digital era